Transformasi Media Pembelajaran Digital dalam Meningkatkan Literasi Sains: Kajian Literatur Sistematis - Wahyuni, Metig Dwi (Balai Diklat Keagamaan Bandung, 2025)
Scientific and digital literacies are essential 21st-century competencies that play a crucial role in supporting innovative learning processes. The digitalization of instructional media has emerged as a strategic approach to enhance students' scientific literacy. This study aims to systematically review existing literature investigating the impact of digital learning media on scientific literacy from 2021 to 2024. A systematic literature review method was employed using the PRISMA protocol, with Google Scholar as the primary database and keywords “digital” and “scientific literacy.” Out of 83 initial articles, 32 met the inclusion criteria after screening. The findings indicate that the most frequently used media in fostering scientific literacy were digital comics (7 articles), e-modules (6 articles), and digital posters (3 articles). These media have demonstrated effectiveness in improving conceptual understanding, critical thinking, and student engagement. The review concludes that digital learning media contribute positively to the development of scientific literacy and are highly relevant for integration into 21st-century education practices. Keywords: digitalization; instructional media; scientific literacy; PRISMA; systematic review